Servant Leadership, Knowledge Management, and Employee Performance of Undata Regional Public Hospital Palu (American Journal of Economics and Business Innovation, 2024)
This research is fundamental because it raises questions about servant leadership, knowledge management, and employee performance in hospitals. This research was designed using a quantitative approach with multiple linear regression analysis. The results of this study indicate that servant leadership and knowledge management on employee performance at Undata Palu Regional General Hospital have a significant effect simultaneously. However, only knowledge management significantly affects employee performance, while servant leadership has no effect. This result means that employee performance in hospitals cannot always be influenced by leadership, but specifically in hospitals, employee performance can be influenced by knowledge management. This is related to the work in hospitals that requires expertise.